Cone-beam computed tomography investigation of middle mesial canals and isthmuses in mandibular first molars in a Chinese population - Xu, Shuaimei (BMC Oral Health, 2020)
BACKGROUND: While there is ample research into the anatomy of mandibular molars, little is known regarding isthmuses and middle mesial (MM) canals in Chinese populations. The goal of this study was to determine the prevalence of MM canals and isthmuses in the mesial root of mandibular first molars using Cone-beam Computed Tomography. METHODS: Cone-beam Computed Tomography images of 357 mature mandibular first molars were retrospectively analyzed. Presence of isthmuses and MM canals, and the length of isthmuses in the mesial root were recorded. Meanwhile, we also recorded possible correlated factors such as demographics, side of mandible, presence of separated distal-lingual roots. RESULTS: Of these 357 teeth, 209 showed evidence of either complete or partial communication in the mesial root. Of these, 11(3.1%) exhibited true MM canals while 198(55.5%) exhibited isthmuses. Sex or side of mandible was not correlated with the prevalence of isthmuses (P > 0.05). However, there was a significant association between the presence of a distal-lingual root and the prevalence of such communication (P < 0.001). The average length of isthmuses was 4.3 ± 3.1 mm. CONCLUSIONS: We detected high rate of isthmuses and low rate of MM canals in mesial roots of mandibular first molars, which is important as such areas should be identified and cleaned during root canal treatment.